Developing a new apathy measurement scale - Radakovic, Ratko (The University of Edinburgh, 2012)
Apathy is both a symptom and syndrome prevalent in many pathological populations that affects motivation to display goal directed functions. Apathy has been established as having a triadic substructure by various researchers but has never been directly detected in normative and non- normative populations. Levy and Dubois (2006) proposed three apathetic subtypes, Cognitive, Emotional- Affective and Auto Activation, all with particular neural correlates and functional impairments. The aim of this study was to create and begin the validation process of a new apathy measure called the Dimensional Apathy Scale (DAS), which assesses the three previously mentioned apathetic subtypes. There were 311 participants (mean = 37.4, SD = 15.0) ranging from 18 to 70 years old .Upon performing an Horn’s parallel analysis of principal factors and Exploratory Factor Analysis, 4 factors (labelled Executive, Emotional, Cognitive Initiation and Behavioural Initiation) were extracted accounting for 28.9% of the total variance. The factors and their meanings fitted Levy and Dubois’ definitions of the three apathetic subtypes with the exception of the Auto Activation apathy. Upon closer examination thematically the Auto Activation apathy subtype definition accounted for Behavioural Initiation and Cognitive Initiation factors. These were found to be thematically intertwined and therefore were labelled as Behavioural/Cognitive Initiation. The 24 item DAS contained 3 subscales – Executive, Emotional and Behavioural/Cognitive Initiation, each composed of 8 items. The DAS items for each subscale showed good reliability and validity against depression based on a normally ageing population. Preliminarily, this serves as evidence for further research using this robust scale and should be further validated in various pathological populations. Research into apathetic subtypes, the DAS scale and implications for eventual clinical use are discussed.
Keywords: Apathy; Apathy Scale; Apathy Subtypes